Characterization and fungicide sensitivity of Trichoderma species causing green mold of Ganoderma sichuanense in China - Li, Xuefei; Sossah, Frederick Leo; Tuo, Yonglan; Hu, Jiajun; Wei, Qian; Li, Shiyu; Rong, Na; Wiafe-Kwagyan, Michael; Li, Changtian; Zhang, Bo; Li, Xiao; Li, Yu (Frontiers in Microbiology, 2023)
Green mold disease, caused by Trichoderma spp., is one of the most devastating diseases of mushrooms in China. The application of fungicides remains one of the important control methods among the integrated pest management tools for disease management in mushroom farms. This study aimed to identify Trichoderma spp., isolated from G. sichuanense fruiting bodies displaying green mold symptoms collected from mushroom farms in Zhejiang, Hubei, and Jilin Province, China, and evaluate their in vitro sensitivity to six fungicides. A total of 47 isolates were obtained and classified into nine Trichoderma spp. namely, T. asperellum, T. citrinoviride, T. ganodermatiderum, T. guizhouense, T. hamatum, T. harzianum, T. koningiopsis, T. paratroviride, and T. virens, through morphological characteristics and phylogenetic analysis of concatenated sequences of translation elongation factor 1-alpha (TEF) and DNA-dependent RNA polymerase II subunit (RPB2) genes. The pathogenicity test was repeated two times, and re-isolation of the nine Trichoderma spp. from the fruiting bodies of G. sichuanense fulfilled Koch’s postulates. Prochloraz manganese showed the best performance against most species. This research contributes to our understanding of green mold disease, reveals the phylogenetic relationships among Trichoderma species, and expands our knowledge of Trichoderma species diversity associated with green mold disease in G. sichuanense.